Preparation technology of nanocrystalline iron core containing flexible epoxy resin for high frequency transformer
By using a bonding curing agent containing flexible epoxy resin, combined with epoxy resin and polyether type polyaryletherketone curing agent, the problems of large brittleness and magnetic properties of the nanocrystalline iron core are solved, and the effect of improving the toughness and magnetic permeability of the nanocrystalline iron core is achieved.
Patent Information
- Application Number
- CN202410740038.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-07
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-06-07
AI Technical Summary
The nanocrystalline iron core is highly brittle after annealing and is difficult to cut and process. The existing curing agent will affect the magnetic properties of the nanocrystalline iron core during the curing process.
A bonding curing agent containing flexible epoxy resin is used to combine the epoxy resin with a polyether polyarylether ketone curing agent to form a new curing system, which consists of 100 parts by weight of epoxy resin and 60-86 parts by weight of polyether polyarylether ketone curing agent, and a nanocrystalline iron core is obtained by dilution, impregnation, vacuum defoaming and heat curing treatment.
The toughness and thermal decomposition temperature of the epoxy resin are improved, the curing shrinkage rate is reduced, the impact on the magnetic properties of the nanocrystal iron core is reduced, and the magnetic permeability retention rate of the nanocrystal iron core is improved.
Smart Images

Figure BDA0004884438250000021 
Figure BDA0004884438250000031 
Figure BDA0004884438250000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanocrystalline iron cores, in particular to a preparation process of a nanocrystalline iron core containing flexible epoxy resin for a high-frequency transformer. Background Art
[0002] Nanocrystalline cores have soft magnetic properties such as high saturation magnetic induction, high initial magnetic permeability, and low high-frequency loss, and are widely used in high-frequency transformers, high-power switching power supplies, high-frequency converters, current transformer cores, etc. However, after the annealing process, the nanocrystalline core is very brittle, and direct cutting will damage the matrix of the nanocrystalline core. Usually, a curing adhesive is needed to encapsulate and solidify the nanocrystalline core to improve its brittleness and facilitate cutting.
[0003] Epoxy resin is an excellent bonding and curing material, and has broad application prospects in the field of encapsulation and curing of materials such as nanocrystalline iron cores. Improving the toughness of epoxy resin, reducing the curing shrinkage and stress generated during curing can reduce the impact of epoxy resin on the magnetic properties of nanocrystalline iron cores. China CN105440887B discloses a special curing agent for nanocrystalline iron cores and a method for curing nanocrystalline iron cores. The curing system composed of high-purity epoxy resin and silica toughening agent, as a special curing agent for nanocrystalline iron cores, has little effect on its soft magnetic properties. The development of new high-performance curing agents can improve the toughness of epoxy resins, without the need to add additional nanoparticle toughening agents such as silica, which can reduce costs and facilitate industrial production and application. Summary of the invention
[0004] The invention provides a flexible epoxy resin adhesive curing agent, which has little effect on the magnetic permeability and other properties of the nanocrystalline iron core.
[0005] Technical solution: A process for preparing a nanocrystalline iron core containing a flexible epoxy resin, wherein the flexible curing agent is composed of 100 parts by weight of epoxy resin and 60-86 parts by weight of a polyether-type polyaryletherketone curing agent;
[0006] The preparation process of the nanocrystalline iron core containing flexible epoxy resin is as follows:
[0007] (1) Fe a S i b B c Nd b Cu e The amorphous strip is wound on a round copper tube and rolled into a ring to make a ring iron core; then it is placed in an annealing furnace, nitrogen is introduced, and amorphous annealing treatment and nanocrystalline annealing treatment are performed in sequence to obtain a nanocrystalline iron core.
[0008] (2) Epoxy resin and polyether-type polyaryletherketone curing agent are added to ethanol for dilution, and then the nanocrystalline iron core is added, impregnated and vacuum degassed, and finally heat-cured to obtain a nanocrystalline iron core containing a flexible epoxy resin.
[0009] Preferably, Fe a S i b B c Nd b Cu e The structural formula is Fe 71-74 S i 13-16 B 7-9 Nd 2.5-3.5 Cu 0.8-1.2 .
[0010] Preferably, the temperature during the amorphous annealing treatment is 375-390° C., and the time is 60-100 min; the temperature during the nanocrystalline annealing treatment is 540-560° C., and the time is 40-60 min.
[0011] Preferably, the thermal curing treatment is first cured at 60-80°C for 2-3 hours, and then cured at 100-120°C for 3-6 hours.
[0012] Preferably, the preparation process of the polyether type polyaryletherketone curing agent is:
[0013] S1. In an ice-water bath, add polyethylene glycol 200-600, p-fluorobenzoyl chloride, and triethylamine in a ratio of 1 mol:(7-10) mol:(7-10) mol to dichloromethane, and then react at room temperature for 18-24 hours, filter, and concentrate the filtrate under reduced pressure, and wash with n-hexane to obtain double-terminated fluorophenyl polyethylene glycol. The reaction formula is:
[0014]
[0015] S2, toluene, 4,4-difluorobenzophenone in a ratio of (0.9-0.98) mol: (0.02-0.1) mol: 1 mol, double-terminated fluorophenyl polyethylene glycol, hydroquinone, and potassium carbonate are added to sulfolane, heated to 150-160°C in a nitrogen atmosphere, azeotropic dehydration for 2-3 hours, then heated to 175-190°C, polymerization reaction for 6-12 hours, finally p-aminophenol is added, reaction is carried out for 1.5-2 hours, after cooling, deionized water is added to dilute, filtered, washed with deionized water and ethanol in turn, and dried to obtain a polyether-type polyaryletherketone curing agent. The reaction route is:
[0016]
[0017] Preferably, the nanocrystalline core containing flexible epoxy resin is used in a high-frequency transformer.
[0018] Technical effect: The present invention utilizes p-fluorobenzoyl chloride and polyethylene glycol to carry out esterification reaction to obtain double-terminal fluorophenyl polyethylene glycol, and then reacts with 4,4-difluorobenzophenone, hydroquinone, and p-aminophenol to obtain a polyether-type polyaryletherketone curing agent. The terminal amino group contained therein can undergo cross-linking and curing with epoxy resin, and the curing agent not only contains polyarylether flexible units, but also contains polyethylene glycol polyether segments with better flexibility, which now improves the bending performance and impact strength of epoxy resin, and is beneficial to improving the toughness and curing shrinkage performance of epoxy resin. In addition, polyaryletherketone has high heat resistance, and as a curing agent, it significantly improves the thermal decomposition temperature and high temperature resistance of epoxy resin. It has broad application prospects in the bonding curing agent of nanocrystalline iron cores, and can meet the practical application of nanocrystalline iron cores in high temperature environments.
[0019] The present invention uses epoxy resin and polyether polyaryletherketone curing agent as the bonding and curing system of the nanocrystalline iron core. The cured epoxy resin has the characteristics of better toughness and low curing shrinkage. After the epoxy resin is bonded and cured with the nanocrystalline iron core, it can prevent the defects and gaps between the epoxy resin and the nanocrystalline iron core caused by the shortcomings of poor toughness and large curing shrinkage of the epoxy resin, thereby affecting the magnetic properties of the nanocrystalline iron core such as inductance and magnetic permeability. At the same time, after curing, the flexible epoxy resin will not produce great stress on the nanocrystalline iron core, but has good filling performance on the nanocrystalline iron core. The magnetic permeability retention rate of the nanocrystalline iron core after bonding and curing is very high, and it still has good magnetic properties. DETAILED DESCRIPTION
[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Example 1
[0022] (1) In an ice-water bath, add 5 mmol polyethylene glycol 600, 40 mmol p-fluorobenzoyl chloride, and 40 mmol triethylamine to 5 mL dichloromethane, and then react at room temperature for 24 h. Filter, concentrate the filtrate under reduced pressure, and wash with n-hexane to obtain double-terminated fluorophenyl polyethylene glycol.
[0023] (2) 10 mL of toluene, 9.8 mmol of 4,4-difluorobenzophenone, 0.2 mmol of double-terminated fluorophenyl polyethylene glycol, 9 mmol of hydroquinone, and 12 mmol of potassium carbonate were added to 15 mL of cyclopentane sulfone, and the mixture was heated to 150° C. in a nitrogen atmosphere for azeotropic dehydration for 3 h, and then heated to 180° C. for polymerization for 8 h. Finally, 0.8 mmol of p-aminophenol was added and the mixture was reacted for 2 h. After cooling, deionized water was added to dilute the mixture, the mixture was filtered, and the mixture was washed with deionized water and ethanol in turn, and dried to obtain a polyether-type polyaryletherketone curing agent.
[0024] (3) Fe 73.5 S i 13.5 The B9Nd3Cu1 amorphous strip is wound on a round copper tube and rolled into a ring to make a ring iron core; then it is placed in an annealing furnace, nitrogen is introduced, and amorphous annealing treatment is performed at 375°C for 100 minutes; then nanocrystalline annealing treatment is performed at 560°C for 40 minutes to obtain a nanocrystalline iron core.
[0025] (4) 500 g of epoxy resin and 430 g of polyether-type polyaryletherketone curing agent were added to 800 mL of ethanol for dilution, and then the nanocrystalline iron core was added, impregnated and vacuum degassed, and cured at 70°C for 2 h, and then cured at 100°C for 6 h to obtain a nanocrystalline iron core containing a flexible epoxy resin.
[0026] Example 2
[0027] (1) In an ice-water bath, add 5 mmol polyethylene glycol 400, 50 mmol p-fluorobenzoyl chloride, and 50 mmol triethylamine to 10 mL dichloromethane, and then react at room temperature for 18 h. Filter, concentrate the filtrate under reduced pressure, and wash with n-hexane to obtain a double-terminated fluorophenyl polyethylene glycol.
[0028] (2) 12 mL of toluene, 9.5 mmol 4,4-difluorobenzophenone, 0.5 mmol double-terminated fluorophenyl polyethylene glycol, 9.3 mmol hydroquinone, and 13 mmol potassium carbonate were added to 20 mL of cyclopentane sulfone, heated to 15°C in a nitrogen atmosphere, and azeotropically dehydrated for 3 hours, and then heated to 175°C for polymerization for 12 hours. Finally, 0.9 mmol p-aminophenol was added and reacted for 2 hours. After cooling, deionized water was added to dilute, filtered, washed with deionized water and ethanol in turn, and dried to obtain a polyether-type polyaryletherketone curing agent.
[0029] (3) Fe 73.5 S i 13.5The B9Nd3Cu1 amorphous strip is wound on a round copper tube and rolled into a ring to make a ring iron core; then it is placed in an annealing furnace, nitrogen is introduced, and amorphous annealing treatment is performed at 375°C for 100 minutes; then nanocrystalline annealing treatment is performed at 550°C for 60 minutes to obtain a nanocrystalline iron core.
[0030] (4) 500 g of epoxy resin and 370 g of polyether-type polyaryletherketone curing agent were added to 800 mL of ethanol for dilution, and then the nanocrystalline iron core was added, impregnated and vacuum degassed, and cured at 80° C. for 2 h, and then cured at 120° C. for 4 h to obtain a nanocrystalline iron core containing a flexible epoxy resin.
[0031] Example 3
[0032] (1) In an ice-water bath, add 5 mmol polyethylene glycol 400, 50 mmol p-fluorobenzoyl chloride, and 50 mmol triethylamine to 10 mL dichloromethane, and then react at room temperature for 18 h. Filter, concentrate the filtrate under reduced pressure, and wash with n-hexane to obtain a double-terminated fluorophenyl polyethylene glycol.
[0033] (2) 10 mL of toluene, 9.3 mmol 4,4-difluorobenzophenone, 0.7 mmol double-terminated fluorophenyl polyethylene glycol, 9.2 mmol hydroquinone, and 12 mmol potassium carbonate were added to 15 mL cyclopentane sulfone, heated to 160° C. in a nitrogen atmosphere, and azeotropically dehydrated for 2 h, then heated to 190° C. and polymerized for 6 h, and finally 0.9 mmol p-aminophenol was added and reacted for 1.5 h. After cooling, deionized water was added to dilute, filtered, washed with deionized water and ethanol in turn, and dried to obtain a polyether-type polyaryletherketone curing agent.
[0034] (3) Fe 73.1 S i 15.5 B 7.4 The Nd3Cu1 amorphous strip is wound on a round copper tube and rolled into a ring to make a ring iron core; then it is placed in an annealing furnace, nitrogen is introduced, and amorphous annealing treatment is performed at 390°C for 60 minutes; then nanocrystalline annealing treatment is performed at 540°C for 60 minutes to obtain a nanocrystalline iron core.
[0035] (4) 500 g of epoxy resin and 370 g of polyether-type polyaryletherketone curing agent were added to 800 mL of ethanol for dilution, and then the nanocrystalline iron core was added, impregnated and vacuum degassed, and cured at 60° C. for 3 h, and then cured at 120° C. for 3 h to obtain a nanocrystalline iron core containing a flexible epoxy resin.
[0036] Example 4
[0037] (1) In an ice-water bath, add 5 mmol polyethylene glycol 200, 35 mmol p-fluorobenzoyl chloride, and 35 mmol triethylamine to 8 mL dichloromethane, and then react at room temperature for 18 h. Filter, concentrate the filtrate under reduced pressure, and wash with n-hexane to obtain a double-terminated fluorophenyl polyethylene glycol.
[0038] (2) 12 mL of toluene, 9 mmol of 4,4-difluorobenzophenone, 1 mmol of double-terminated fluorophenyl polyethylene glycol, 9.3 mmol of hydroquinone, and 13 mmol of potassium carbonate were added to 20 mL of cyclopentane sulfone, heated to 150° C. in a nitrogen atmosphere, and subjected to azeotropic dehydration for 3 h. The mixture was then heated to 180° C. and subjected to polymerization for 12 h. Finally, 0.8 mmol of p-aminophenol was added and reacted for 2 h. After cooling, the mixture was diluted with deionized water, filtered, washed with deionized water and ethanol in turn, and dried to obtain a polyether-type polyaryletherketone curing agent.
[0039] (3) Fe 73.1 S i 15.5 B 7.4 The Nd3Cu1 amorphous strip is wound on a round copper tube and rolled into a ring to make a ring iron core; then it is placed in an annealing furnace, nitrogen is introduced, and amorphous annealing treatment is performed at 380°C for 100 minutes; then nanocrystalline annealing treatment is performed at 540°C for 60 minutes to obtain a nanocrystalline iron core.
[0040] (4) 500 g of epoxy resin and 300 g of polyether-type polyaryletherketone curing agent were added to 800 mL of ethanol for dilution, and then the nanocrystalline iron core was added, impregnated and vacuum degassed, and cured at 60° C. for 3 h, and then cured at 110° C. for 4 h to obtain a nanocrystalline iron core containing a flexible epoxy resin.
[0041] Comparative Example 1
[0042] (1) 10 mL of toluene, 9.8 mmol of 4,4-difluorobenzophenone, 9 mmol of hydroquinone, and 12 mmol of potassium carbonate were added to 15 mL of cyclopentane sulfone, and the mixture was heated to 150° C. in a nitrogen atmosphere for azeotropic dehydration for 3 h, and then heated to 180° C. for polymerization for 8 h. Finally, 0.8 mmol of p-aminophenol was added and the mixture was reacted for 2 h. After cooling, deionized water was added to dilute the mixture, the mixture was filtered, and the mixture was washed with deionized water and ethanol in turn, and dried to obtain a polyaryletherketone curing agent.
[0043] (2) Prepare a nanocrystalline iron core according to the method of Example 1.
[0044] (3) 500 g of epoxy resin and 430 g of polyaryletherketone curing agent were added to 800 mL of ethanol for dilution, and then the nanocrystalline iron core was added, impregnated and vacuum degassed, and cured at 70° C. for 2 h, and then cured at 100° C. for 6 h to obtain a nanocrystalline iron core containing a flexible epoxy resin.
[0045] Comparative Example 2
[0046] (1) Prepare a nanocrystalline iron core according to the method of Example 1.
[0047] (2) 500 g of epoxy resin and 430 g of polyetheramine D2000 as a curing agent were added to 800 mL of ethanol for dilution, and then the nanocrystalline iron core was added, impregnated and vacuum degassed, and cured at 70° C. for 2 h, and then cured at 100° C. for 6 h to obtain a nanocrystalline iron core containing a flexible epoxy resin.
[0048] Taking Example 1 as an example, 500 g of epoxy resin and 430 g of polyether-type polyaryletherketone curing agent were added to 800 mL of ethanol for dilution, vacuum degassing, and cured at 70° C. for 2 h, and then cured at 100° C. for 6 h to obtain a flexible epoxy resin cured product.
[0049] The flexural strength and impact strength of the cured product are tested according to GB / T 2567-2021 method.
[0050] The thermal properties of the cured product were tested by a thermogravimetric analyzer in a nitrogen atmosphere with a heating rate of 10°C / min.
[0051] Table 1 Epoxy resin performance test
[0052]
[0053] The inductance L of the nanocrystalline iron core containing flexible epoxy resin before and after curing was measured using an inductance tester. The magnetic permeability retention was calculated. W = u1 / u2 × 100%. u1 is the magnetic permeability of the nanocrystalline iron core after curing. u2 is the magnetic permeability of the nanocrystalline iron core before curing.
[0054] Magnetic permeability u=(L×d) / (4πSN 2 ). L is the inductance; d is the effective magnetic path length. S is the effective cross-sectional area. N is the number of coil turns of the nanocrystalline core.
[0055] Table 2 Magnetic permeability retention test of nanocrystalline core
[0056] Magnetic permeability retention (%) Example 1 94.4 Example 2 93.8 Example 3 88.5 Example 4 91.0 Comparative Example 1 62.7 Comparative Example 2 77.3
[0057] As shown in Table 1, in Examples 1 to 4, epoxy resin and polyether polyaryletherketone curing agent are used as the curing system, the bending strength of the epoxy resin is 102.3-125.9MPa, and the impact strength reaches 16.3-22.6kJ / m 2 , and the thermal decomposition temperature of 5% mass loss reaches 396.3-403.0℃. This is because the terminal amino group contained in the added polyether-type polyaryletherketone curing agent can be cross-linked and cured with the epoxy resin, and the curing agent not only contains polyarylether flexible units, but also contains polyethylene glycol polyether segments with better flexibility. Now the bending properties and impact strength of the epoxy resin are improved, which is beneficial to improve the toughness and curing shrinkage properties of the epoxy resin. In addition, polyaryletherketone has high heat resistance. As a curing agent, it significantly improves the thermal decomposition temperature and high temperature resistance of the epoxy resin. It has broad application prospects in the bonding curing agent of nanocrystalline iron cores, which can meet the practical application of nanocrystalline iron cores in high temperature environments.
[0058] In Comparative Example 1, no double-terminal fluorophenyl polyethylene glycol was added when preparing the polyaryletherketone curing agent, resulting in the polyaryletherketone molecular chain not containing flexible polyethylene glycol polyether segments, poor toughening effect on epoxy resin, and low bending strength and impact strength.
[0059] In Comparative Example 2, polyetheramine D2000 is used as the curing agent. The bending strength and impact strength of the epoxy resin are poor, and the thermal decomposition temperature is low, and the high temperature resistance is poor.
[0060] The present invention uses epoxy resin and polyether polyaryletherketone curing agent as the bonding and curing system of the nanocrystalline iron core. The cured epoxy resin has the characteristics of better toughness and low curing shrinkage. After the epoxy resin and the nanocrystalline iron core are cured, it can prevent the defects and gaps between the epoxy resin and the nanocrystalline iron core caused by the shortcomings of poor toughness and large curing shrinkage of the epoxy resin, thereby affecting the magnetic properties of the nanocrystalline iron core such as inductance and magnetic permeability. At the same time, after curing, the flexible epoxy resin will not produce great stress on the nanocrystalline iron core, but has good filling performance on the nanocrystalline iron core. The magnetic permeability retention rate of the nanocrystalline iron core after bonding and curing is very high, and it still has good magnetic properties.
[0061] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which shall fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A process for preparing a nanocrystalline iron core containing a flexible epoxy resin, characterized in that: The flexible epoxy resin is composed of 100 parts by weight of epoxy resin and 60-86 parts by weight of polyether type polyaryletherketone curing agent; The preparation process of the nanocrystalline iron core containing flexible epoxy resin is as follows: (1) Fe a Si b B c Nd b Cu e The amorphous strip is wound on a round copper tube and rolled into a ring to make a ring iron core; then it is placed in an annealing furnace, nitrogen is introduced, and amorphous annealing treatment and nanocrystalline annealing treatment are performed in sequence to obtain a nanocrystalline iron core; (2) adding epoxy resin and polyether type polyaryletherketone curing agent into ethanol for dilution, then adding nanocrystalline iron core, impregnating and vacuum degassing, and finally performing heat curing treatment to obtain nanocrystalline iron core containing flexible epoxy resin; The Fe a Si b B c Nd b Cu e The structural formula is Fe 71-74 Si 13-16 B 7-9 Nd 2.5-3.5 Cu 0.8-1.2 ; The preparation process of the polyether type polyaryletherketone curing agent is as follows: S1, in an ice water bath, adding polyethylene glycol, p-fluorobenzoyl chloride and triethylamine to dichloromethane, then reacting at room temperature for 18-24 hours, filtering, concentrating the filtrate under reduced pressure, and washing with n-hexane to obtain double-terminated fluorophenyl polyethylene glycol; S2, toluene, 4,4-difluorobenzophenone, double-terminated fluorophenyl polyethylene glycol, hydroquinone, potassium carbonate are added to sulfolane, heated in a nitrogen atmosphere for azeotropic dehydration, and then a polymerization reaction is carried out, and finally p-aminophenol is added to react, and after cooling, deionized water is added to dilute, filter, wash with deionized water and ethanol in turn, and dry to obtain a polyether-type polyaryletherketone curing agent; In S1, the ratio of polyethylene glycol, p-fluorobenzoyl chloride and triethylamine is 1 mol:(7-10) mol:(7-10) mol; the molecular weight of polyethylene glycol is 200-600; In S2, the ratio of 4,4-difluorobenzophenone, double-terminated fluorophenyl polyethylene glycol, and hydroquinone is (0.9-0.98) mol: (0.02-0.1) mol: 1 mol.
2. The process for preparing a nanocrystalline iron core containing a flexible epoxy resin according to claim 1, characterized in that: The temperature during the amorphous annealing treatment is 375-390° C., and the time is 60-100 min; the temperature during the nanocrystalline annealing treatment is 540-560° C., and the time is 40-60 min.
3. The process for preparing a nanocrystalline iron core containing a flexible epoxy resin according to claim 1, characterized in that: The heat curing treatment is firstly cured at 60-80°C for 2-3 hours, and then cured at 100-120°C for 3-6 hours.
4. The process for preparing a nanocrystalline iron core containing a flexible epoxy resin according to claim 1, characterized in that: The temperature of the azeotropic dehydration is 150-160° C., and the time is 2-3 hours; the polymerization reaction temperature is 175-190° C., and the time is 6-12 hours.
5. Use of a nanocrystalline iron core containing flexible epoxy resin obtained by the preparation process according to any one of claims 1 to 4 in a high-frequency transformer.
Citation Information
Patent Citations
Nanocrystalline iron core special-purpose curing agent and nanocrystalline iron core curing method
CN105440887A
Toughener and modified epoxy resin
CN105623265A